STUDI MENGENAI PERAN KEPERCAYAAN DALAM MEMEDIASI MOTIVASI SOSIAL DAN SOCIAL MEDIA INFLUENCER TERHADAP MINAT BELI (Produk Skincare Somethinc di Semarang) - Tri Sumaryati, Amelia Rahmadani; Indriani, Farida (Diponegoro Journal of Management, 2024)
ABSTRACT This research aims to explore how trust plays a mediating role in the relationship between social motivation and social media influencers regarding purchase intention for the skincare brand “Somethinc”. Trust represents consumer’s tendency to rely on a particular brand in expressing either explicit or implicit commitment. The study employed a survey method using a Google Form questionnaire distributed to the residents of Semarang City who are familiar with the Somethinc skincare brand and are planning to purchase Somethinc skincare products. The collected data were analyzed using the SPSS software analysis technique. Additionally, the sobel test was conducted to examine the relationship between the mediation variables in this research. The research results indicate that social motivation and social media influencers have a direct impact on purchase intention. However, trust does not significantly influence purchase intention. Furthermore, social motivation and social media influencers influence trust. The findings also reveal that trust cannot mediate the relationship between social motivation and social media influencers on purchase intention. This evident in the case study of the Somethinc skincare brand in the Semarang City area.